2021
DOI: 10.1007/s10546-021-00653-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of Strong Flux Underestimation by Bulk Parametrizations During Drifting and Blowing Snow

Abstract: The influence of drifting and blowing snow on surface mass and energy exchange is difficult to quantify due to limitations in both measurements and models, but is still potentially very important over large areas with seasonal or perennial snow cover. We present a unique set of measurements that make possible the calculation of turbulent moisture, heat, and momentum fluxes during conditions of drifting and blowing snow. From the data, Monin–Obukhov estimation of bulk fluxes is compared to eddy-covariance-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
2
29
1
Order By: Relevance
“…Based on the fact that saltation snow particles are broken and become spherical balls by continuous collisions with the surface (Sato et al, 2008;Okaze et al, 2018), we considered snowflakes as spherical balls and use equivalent diameter to describe different shapes of snowflakes in the simulation. And this is consistent with the major works in 1) numerical simulation of drifting snow physical process using Eulerian-Lagrangian (Schmidt, 1980;Nemoto and Nishimura, 2004;Groot Zwaaftink et al, 2014;Li et al, 2017;Wang and Huang, 2017;Melo et al, 2022;Sigmund et al, 2022) and 2) site observation in estimating the mass flux and particle size distribution (Guala et al, 2008;Crivelli et al, 2016). Drag force-when particle velocity differs from the fluid velocity, fluid has a drag effect on the particles:…”
Section: Particle Movement Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on the fact that saltation snow particles are broken and become spherical balls by continuous collisions with the surface (Sato et al, 2008;Okaze et al, 2018), we considered snowflakes as spherical balls and use equivalent diameter to describe different shapes of snowflakes in the simulation. And this is consistent with the major works in 1) numerical simulation of drifting snow physical process using Eulerian-Lagrangian (Schmidt, 1980;Nemoto and Nishimura, 2004;Groot Zwaaftink et al, 2014;Li et al, 2017;Wang and Huang, 2017;Melo et al, 2022;Sigmund et al, 2022) and 2) site observation in estimating the mass flux and particle size distribution (Guala et al, 2008;Crivelli et al, 2016). Drag force-when particle velocity differs from the fluid velocity, fluid has a drag effect on the particles:…”
Section: Particle Movement Modelsupporting
confidence: 88%
“…Future work, will therefore address these limitations and attempt to include electrostatic forces in a saltation model such as the CRYOS LES (Sharma et al, 2018). A main aspect of this future work should be on dynamically modelling charging of particles and on analysing the influence on total mass flux and sublimation (Sigmund et al, 2022). Overall, this will allow for a better understanding of the momentum/energy transfer near the surface under the effect of the strong electric field in drifting snow, and this can support a theoretical basis for the solving interfere of radiation communication in blizzards.…”
Section: Discussionmentioning
confidence: 99%
“…The high snow transport rates are also a result of the relatively low aerodynamic roughness length of sea ice, where z 0 is typically lower for first-year ice (FYI) than for second-or multi-year ice (SYI or MYI) (Weiss et al, 2011). In addition, large parts of the snow mass can be expected to get blown into leads or undergo sublimation (Déry and Yau, 2002;Déry and Tremblay, 2004;Leonard and Maksym, 2011;Liston et al, 2020), which has recently been shown to be underestimated by current models (Sigmund et al, 2022). Besides thermodynamic ice growth at its bottom, snow can directly contribute to ice formation on top of the sea ice as snow ice.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Town and Walden (2009) found for measurements at the South Pole station that the bulk approach underestimates the LHF by 40-60 % compared to observations obtained using the direct EC method. Sigmund et al (2022) observed a three times smaller flux using a bulk approach compared to the EC method during a storm period at the Syowa S17 station in East Antarctica. They find a flux underestimation using a bulk approach of 16-20 % with blowing snow turned off in their simulations and even 70-87 % when blowing snow is enabled.…”
Section: Introductionmentioning
confidence: 88%